Inovasi Kebudayaan: Tari Chit Ngiat Pan: Refleksi Hubungan Sosial atas Semboyan “Tong Ngin Fan Ngin Jit Jong” - Yessi Nirmala; Aimie Sulaiman; Jamilah Cholillah (Jurnal Studi Inovasi, 2021)
This study analyzes innovation, one of which is cultural innovation. The culture studied is a culture that is formed as the result of cultivation or human creativity which is called art, especially dance art. The focus of this research is to discuss the reflection of social relations on the motto "Tong Ngin Fan Ngin Jit Jong" in Chit Ngiat Pan Dance. The method used in this study was a qualitative method with an interpretive analysis approach. In addition, the data were collected by observation technique, informant interview determined by purposive sampling technique, and documentation. In order to analyze this study, the theory of Symbolic Interactionism by Herbert Blumer is applied with three main principles, namely meaning, language, and thought. The researcher uses dance symbols as the unit of analysis, which are movement, fashion, and make-up. The meaning of the Chit Ngiat Pan Dance shows an adjustment to the meaning of solidarity, namely "Tong Ngin Fan Ngin Jit Jong" which is explored through the dance symbols. This motto is the key to the creation of the Chit Ngiat Pan Dance aside from promoting Chinese ethnic culture. Language is obtained as the result of the interaction among fellow dancers, that the Chit Ngiat Pan Dance was initially created for the purpose of competition. Thought is a goal to gain victory in the competition in order to advance to the international stage. The use of the motto "Tong Ngin Fan Ngin Jit Jong" has created acculturation which shows the solidarity between Malay and Chinese ethnic groups in Bangka Belitung represented through the dance art. Keywords: Cultural innovation, solidarity reflection, acculturation